AI IN MULTIDISCIPLINARY EDUCATIONAL MANAGEMENT DESIGN - Suprun, Daria (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The question of AI in multidisciplinary Educational Management design has been raised. The integration of AI into education as modern scientific approach, trend with leading characteristics, advantages and disadvantages has been delighted. Practical examples and recommendations: how to provide AI in multidisciplinary Educational Management design, were given.